THE INFLUENCE OF THE EXTRACTION TEMPERATURE ON THE RENDEMENT AND PECTIN METHOXYL CONTENTS OF WATERHYACINTH (Eichornia crassipes (Mart) Solms) - Ika Daniarsari; Nurul Hidajati (Universitas Gadjah Mada, 2005)
The purpose of this research is to find out the influence of the extraction temperature on the rendement and pectin methoxyl contents of waterhyacinth with the applied temperatures ranged from 60, 70, 80, 90 and 100 °C.The stages of this research involve extraction, precipitation, washing and drying. The pectin produced was, then, identified by reacting it with water, ethanol 96 %, NaOH and spectrophotometer IR. Its product was, then, compared to the comparing pectin. To determine the methoxyl contents, the acid - base titration was used. The resulting data were analysed and tested using One Direction Anava with SPSS 10.0 program. From the quantitative used by this study, pectin was produced. This is shown by the gel-formation. The rendements produced with the extraction temperatures of 60, 70, 80, 90 and 100 °C were 0,428 %; 0,487 %; 0,629 %; 0,774 % and 0,958% respectively. While its methoxyl contents were 3,879 %; 3,993 %; 4,413 %; 3,573 % and 2,837 %. Based on the analysed data, it was found that the treatment with the extraction temperature gives a significant influence on the rendement and pectin methoxyl contents of waterhyacinth.